Il-6 signaling between ductal carcinoma in situ cells and carcinoma-associated fibroblasts mediates tumor cell growth and migration. Issue 1 (December 2015) - Osuala, Kingsley; Sameni, Mansoureh; Shah, Seema; Aggarwal, Neha; Simonait, Michelle; Franco, Omar; Hong, Yan; Hayward, Simon; Behbod, Fariba; Mattingly, Raymond; Sloane, Bonnie
Abstract Background Ductal carcinoma in situ (DCIS) is a non-obligate precursor lesion of invasive breast cancer in which approximately half the patients will progress to invasive cancer. Gaining a better understanding of DCIS progression may reduce overtreatment of patients. Expression of the pro-inflammatory cytokine interleukin-6 increases with pathological stage and grade, and is associated with poorer prognosis in breast cancer patients. Carcinoma associated fibroblasts (CAFs), which are present in the stroma of DCIS patients are known to secrete pro-inflammatory cytokines and promote tumor progression. Methods We hypothesized that IL-6 paracrine signaling between DCIS cells and CAFs mediates DCIS proliferation and migration. To test this hypothesis, we utilized the mammary architecture and microenvironment engineering or MAME model to study the interactions between human breast CAFs and human DCIS cells in 3D over time. We specifically inhibited autocrine and paracrine IL-6 signaling to determine its contribution to early stage tumor progression. Results Here, DCIS cells formed multicellular structures that exhibited increased proliferation and migration when cultured with CAFs. Treatment with an IL-6 neutralizing antibody inhibited growth and migration of the multicellular structures. Moreover, selective knockdown of IL-6 in CAFs, but not in DCIS cells, abrogated the migratory phenotype. Conclusion Our results suggest that paracrine IL-6 signaling between preinvasive DCIS cells and stromal CAFs represent an important factor in the initiation of DCIS progression to invasive breast carcinoma.